Ethnography and the digital scenario: a typological scheme of differences and evolutionary trajectories - Padricelli, Giuseppe Michele; Punziano, Gabriella (Frontiers in Sociology, 2023)
The ethnographic method has been a feature of the social sciences since its inception, and for some disciplines, it is markedly characterised by a strong aptitude for physical field research over extended periods in circumscribed communities. However, with the advent of the digital age, this process has undergone further acceleration, upsetting and partly undermining the solid assumptions on which the ethnographic method had been formed, precisely because in the digital scenario, the assumptions of boundaries of contexts, the agency of scenario and the need for a long-term field investigation change radically. This conceptual analysis aims at providing an overview of the trajectory of the evolution of ethnographic studies in social sciences by trying to trace the main pillars of change and the future direction of the method.